PENGARUH KUALITAS PELAYANAN, KEPUASAN DAN NILAI NASABAH TERHADAP LOYALITAS NASABAH SIMPAN PINJAM PADA KUD “TANI JAYA” KECAMATAN PUNCU - Nurfadila, Kharisma (Universitas Nusantara PGRI Kediri, 2023)
This study generally aims to determine the effect of service quality, satisfaction and value of savings and loan customers on customer loyalty at the Village Unit Cooperative